IMPROVING THE EFFICIENCY OF RAIL TRANSPORT: THE WORLD EXPERIENCE - EGAMBERDIEVA KHURSHIDAKHON ALISHEROVNA (TADQIQOTLAR, 2025)
Railroad  transportation  is  a  complex  system  of  a  country's  economy.  In  a situation  where  managing  a  simple  system  requires  a  special  approach,  a  complex system such as railroad transportation must be based on well-designed and effective principles  for  the  entire  country.  In  recent  years,  many  countries  have  undergone various forms of railroad reform. The most common of these is the process of vertically integrated liberalization. This article examines the achievements and consequences of this process in different countries. The purpose of the study is to examine changes in the global transport system as an experiment, i.e. to determine the feasibility of such processes as privatization and liberalization of rail transport in different countries on the railroads of Uzbekistan.[1] As  mentioned  above,  when  implementing  reforms  or  changes  related  to  the liberalization of rail transport, it is necessary to analyze its competitiveness in different countries, because any action to be taken on rail transport should ultimately improve its operational efficiency. Consequently, it is necessary to assess the importance of railroad  liberalization  in  terms  of  improving  the  efficiency  of  railroad  operations through indicators of competitiveness.[2]